Book Review: Making Thinking Visible - Royal, Kenneth; Hardie, Lizette (Canadian Medical Education Journal, 2015)
Recent trends in medical education emphasize the importance of producing well-rounded graduates who not only possess a sufficient fund of medical knowledge but who can think clearly and deeply. Unfortunately, many medical educators struggle with what exactly it means to “think” and do not know where to begin when asked to teach “thinking.” We believe the book Making Thinking Visible, though written for K-12, will be of great interest to medical educators. The book describes different types of thinking and presents more than 20 teaching routines that can help engage learners and improve learning to think.